PENGARUH PENERAPAN ACTIVITY BASED COSTING (ABC) TERHADAP MANAJEMEN BIAYA PRODUKSI, PRODUKTIVITAS PERUSAHAAN, DAN EFISIENSI PERUSAHAAN - Tahang, Moh; Hakim, Melati Puspita (JURNAL LENTERA AKUNTANSI, 2023)
This study aims to analyze the influence of the implementation of activity-based costing (ABC) on the management of production costs, productivity and efficiency of the company. The research method used is qualitative with case studies in several manufacturing companies that have implemented the ABC system. Data collection is done through in-depth interviews with production managers, analysis of financial statements and direct observation of the production process. This study was conducted for 6 months, from January to June. The results show that the implementation of ABC has a significant impact on the company's production cost management. With ABC, companies can more accurately determine the cost of production for each activity involved, helping to make resource allocation decisions and control costs more accurately. Furthermore, the adoption of ABC is also associated with increasing the company's productivity. With a better understanding of production costs, companies can optimize production processes and improve overall operational efficiency. However, this study has some limitations, including limited case study and focus on qualitative data. The implication of this study is the importance of how companies view the implementation of ABC as a tool to improve cost management, productivity and operational efficiency in order to gain a competitive advantage.  Keywords: Activity Based Costing, Production Cost Management, Company Productivity, Company Efficiency